2020
DOI: 10.1093/pm/pnaa221
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Empirical Evaluation of a Quality Indicator System for Postoperative Pain Management

Abstract: Objectives This study aimed to establish a quality indicator system for postoperative pain management and test its reliability, validity, and discrimination in China. Methods We established a quality indicator system using the Delphi method. Further, we designed and administered a survey questionnaire in the orthopedic departments of nine hospitals, located in the Zhejiang and Jiangsu Provinces, through purposive and convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nurses selected assessment tools according to the age and speci c conditions of patients, from the Numerical Rating Scale (NRS), Verbal Descriptor Scale (VDS), and Faces Pain Scale-Revised (FPS-R). The NRS was composed of 11 numbers with the same interval from 0 to 10: no pain (0), mild pain (1-3), moderate pain (4-6), and severe pain (7)(8)(9)(10). VDS used "no pain, mild pain, moderate pain, severe pain, severe pain, and the most pain" to represent different levels of pain intensity.…”
Section: Preliminary Preparation Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses selected assessment tools according to the age and speci c conditions of patients, from the Numerical Rating Scale (NRS), Verbal Descriptor Scale (VDS), and Faces Pain Scale-Revised (FPS-R). The NRS was composed of 11 numbers with the same interval from 0 to 10: no pain (0), mild pain (1-3), moderate pain (4-6), and severe pain (7)(8)(9)(10). VDS used "no pain, mild pain, moderate pain, severe pain, severe pain, and the most pain" to represent different levels of pain intensity.…”
Section: Preliminary Preparation Workmentioning
confidence: 99%
“…A review of relevant literature found that scholars from all over the world have mainly used different methods to construct evaluation systems to evaluate the quality of hospital nursing and pain nursing management. For example, Chen Jiajia et al constructed the quality index system of postoperative pain management in China through the Delphi method, including a total of 43 evaluation indicators from three aspects of structure, process, and result, to evaluate the quality of postoperative pain management [10]. However, there are many complicated indicators and it is not easy to promote in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…14 Most of the published studies on acute postoperative pain in China mainly limited in specific region or a certain type of surgery, and the patient sample were much small. 15 , 16 , 17 In the PAIN-OUT China study, 18 , 19 , 20 we studied acute postoperative pain in 2520 patients from 12 hospitals, from which we got a preliminary understanding of acute postoperative pain in China. Considering the large number of hospitals in China and the significant variation in medical levels among regions, in this study we conducted a survey with 122 research centers to evaluate the current status of acute postoperative pain in China.…”
Section: Introductionmentioning
confidence: 99%